Effect of dietary volatile fatty acid on the blood metabolites in buffalo male calves - Vidyarathi, V K; Kurar, C K (The Indian Journal of Animal Sciences, 2012)
Male buffalo calves (18) were allotted in 3 groups. Six buffalo calves (group 1, control) were fed with whole milk, skimmed milk, calf starter and green fodder. Six calves (group 2) were fed with same feeding schedule as in group 1 along with propionic acid @ 24 ml / calf / day. Six buffalo calves of group 3 were fed with the same feeding schedule as per control group along with 24 ml of butyric acid / calf / day. Three calves from each group were sacrificed at the age of 60 days and the remaining were reared up to 120 days. Average concentrations of blood glucose was significantly (P